Pengaruh Intellectual Capital dan Laverage Pada Profitabilitas - Manurung, Carolina Lidya; Syahzuni, Barlia Annis (Jurnal Riset Akuntansi Politala, 2024)
The COVID-19 pandemic has had a negative impact on various business sectors in Indonesia, including the property and real estate sector. However, the property and real estate sector still made a significant contribution (16%) to Indonesia's GDP (Public Relations Secretariat of the Republic of Indonesia Cabinet, 2023). This indicates that the sector has managed to maintain its performance and withstand the economic crisis. This research aims to investigate the influence of intellectual capital and leverage on the profitability of companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The study employs a quantitative method using multiple linear regression. The research population includes all property and real estate companies listed on the IDX from 2020 to 2022, with a sample size of 96 financial reports from 32 companies obtained through purposive sampling. The results of the study show that intellectual capital significantly has a positive impact on profitability. Conversely, leverage significantly has a negative impact on profitability.